EFEKTIFITAS RETRIBUSI SAMPAH TERHADAP PENDAPATAN ASLI DAERAH KOTA AMBON. - LATUAMURY, SHERLIE EVABIONI; LATUCONSINA, SATIAH (Journal of Applied Accounting, 2023)
The aim of this research is to determine the effectiveness of waste levies on regional original income. The data used in this research is data from 2020 to 2022.The research method used in this research is the contribution method. The data collection technique used by researchers is direct interviews with the objects studied, field observations and literature. The type of data used is quantitative data while the data source comes from primary data and secondary data.The results of research using the contribution method show that the waste levy has increased very effectively every year, where in 2020 the levy reached 103.53% with an income of Rp. 6,734,688,000.00, in 2021 it will reach 107.08% with income of Rp. 6,978,881,720.00, and in 2022 it will reach 107.28% with income of Rp. 6,978,881,720.00 than targeted. Keywords: effectiveness, waste levy, local original income.